Effects of a community-driven water, sanitation and hygiene intervention on water and sanitation infrastructure, access, behaviour, and governance: a cluster-randomised controlled trial in rural Democratic Republic of Congo. Issue 5 (17th May 2021) - Quattrochi, John Paul; Coville, Aidan; Mvukiyehe, Eric; Dohou, Caleb Jeremie; Esu, Federica; Cohen, Byron; Bokasola, Yannick Lokaya; Croke, Kevin
Abstract : Introduction: Inadequate water and sanitation is a central challenge in global health. Since 2008, the Democratic Republic of Congo government has implemented a national programme, Healthy Villages and Schools ( Villages et Ecoles Assainis (VEA), with support from UNICEF, financed by UK's Foreign, Commonwealth and Development Office. Methods: A cluster-level randomised controlled trial of VEA was implemented throughout 2019 across 332 rural villages, grouped into 50 treatment and 71 control clusters. Primary outcomes included time spent collecting water; quantity of water collected; prevalence of improved primary source of drinking water; and prevalence of improved primary defecation site. Secondary outcomes included child health, water governance, water satisfaction, handwashing practices, sanitation practices, financial cost of water, school attendance and water storage practices. All outcomes were self-reported. The primary analysis was on an intention-to-treat basis, using linear models. Outcomes were measured October–December 2019, median 5 months post-intervention. Results: The programme increased access to improved water sources by 33 percentage points (pp) (95% CI 22 to 45), to improved sanitation facilities by 26 pp (95% CI 14 to 37), and improved water governance by 1.3 SDs (95% CI 1.1 to 1.5), water satisfaction by 0.6 SD (95% CI 0.4 to 0.9), handwashing practices by 0.5 SD (95% CI 0.3 to 0.7) and sanitation practices by 0.3 SD (95% CI 0.1 to 0.4). There was no significant difference in financial cost of water, school attendance, child health or water storage practices. Conclusion: VEA produced large increases in access to and satisfaction with water and sanitation services, in self-reported hygiene and sanitation behaviour, and in measures of water governance. Trial registration number: AEARCTR-0004648; American Economic Association RCT registry.